Mengungkap Makna Puitik dalam Lagu Yā ‘Āsyiqah al-Ward Karya Zaki Nassif: Analisis Semiotika Michael Riffaterre - Bayu Ihsan Sauqi; Akmaliyah Akmaliya; Khomisah Khomisah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
This study aims to uncover the mechanism of the shift in meaning from aesthetic romanticism to moral guidance in contemporary Arabic literary works. The main data source used in this study is specifically the lyric text of the song